Thermodynamics foundations and applications - Gyftopoulos, E. P. (Dover Publications, 2005)
Designed by two MIT professors, this authoritative text transcends the limitations and ambiguities of traditional treatments to develop a deep understanding of the fundamentals of thermodynamics and its energy-related applications. Basic concepts and applications are discussed in complete detail, with attention to generality, rigorous definitions, and logical consistency. More than 300 solved problems span a wide range of realistic energy systems and processes.
"An augmented and corrected republication of the work originally published by Macmillan Publishing Company, New York, in 1991"--T.p. verso.
Includes index.
Keywords: Thermodynamics -- Textbooks.; elektronické knihy; electronic books